Assessing Secondary Students’ Attitudes Toward Global Warming - Bayu Eka Putra; Andi Suhandi; Lina Aviyanti; Mohd Zaidi Bin Amiruddin; Khairun Nisa' (Universitas Lambung Mangkurat, 2025)
Global warming constitutes a critical topic that must be understood by students, given its far-reaching impacts on the environment, human life, and planetary sustainability. Students’ attitudes and responses toward the causes, consequences, and mitigation strategies of global warming play a pivotal role in fostering ecological awareness and promoting environmentally responsible behavior from an early age. This study aims to explore students' attitudes toward global warming in the context of physics education, focusing on their understanding of the issue and its impact on their perspectives on related policies and actions. This study employed a quantitative approach involving 40 tenth-grade students from a senior high school in Indonesia who were studying under the Kurikulum Merdeka. Data were collected using a 4-point Likert scale that measured students' attitudes towards seven main aspects related to global warming. The results showed that the majority of students have a positive attitude towards integrating material on global warming into physics learning and demonstrate awareness of the importance of addressing this issue. However, there are differences of opinion regarding policies on the use of fossil energy and alternative energy. Some students still show a conservative attitude towards fossil energy policies, while others support the policy of using alternative energy that is more environmentally friendly. This study provides important insights into the importance of integrating environmental issues in physics education and its role in shaping a younger generation that is more aware of climate change. The findings are expected to contribute to the development of educational programs that are more relevant and meaningful in raising environmental awareness and sustainability among students.